Partisipasi Masyarakat Lokal Dalam Pengelolaan Daya Tarik Wisata Air Terjun Sipiso-piso Kabupaten Karo, Sumatera Utara - Sitanggang, Louis Steven; Sugiarti, Dian Pramita (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p11, 2020)
Sipiso-piso Waterfall located in Karo District, North Sumatra can be used as a superior attraction because it has great potential to be developed compared to other attractions around Lake Toba because this waterfall is one of the most popular tourist attractions. However, there are several obstacles on the development of Sipiso-piso Waterfall tourism such as tourism stakeholders who do not cooperate well such as the provision of supporting facilities that should be provided by the tour manager, namely the Karo District government instead, provided by the local community. Based on this phenomenon, it is necessary to know the management of Sipiso-piso Waterfall and how much participation of local people in the management of Sipiso-piso Waterfall. The method used in this research is descriptive qualitative. This research aims to To find out how to manage Sipiso-piso waterfall in Karo District, North Sumatra To find out how far the participation of local people in the management of Sipiso-piso waterfall. D ata collection techniques using observation, interviews, and literature. Determination of informants using Purposive Sampling techniques. The results of this research is that the  community in the management of Sipiso-Piso Water Tourism Attraction at the planning stage is at the encouraged participation type, at the community organizing stage is at the spontaneous participation as well as at the mobilization stage, while at the community supervision stage is at the encouraged participation type.   Keywords: participation, development, local community